THE ROLE OF NATURAL ANTIOXIDANTS AS POTENTIAL THERAPEUTIC AGENT IN NEPHROLITHIASIS - DEEPIKA, AGGARWAL; MINU, SHARMA; SURINDER K, SINGLA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Renal injury and inﬂammation caused by ROS play a major role in stone formation. Under the hyperoxaluric condition, crystal deposition results in angiotensin II (Ang II) activation. NADPH Oxidase is stimulated by activated Ang II, leading to ROS production, which can damage renal cells. Oxidative stress also results in mitochondrial dysfunction and release of pro-apoptotic factors from depolarized mitochondria that result in apoptosis that leads to renal injury. Crystal retention in the kidney requires tubular epithelial injury accompanied by luminal expression of HA, OPN, and CD44. The expression of these molecules turns a non–crystal-binding epithelium into a crystal-binding one, thereby setting the stage for crystal retention. Recently many antioxidants have been studied that prevent hyperoxaluria mediated nephrolithiasis. Antioxidant treatment significantly reduces CaOx crystal deposition in kidneys. Naturally occurring antioxidants such as Vitamin E, Apocynin, Phycocyanin, Fucoidin, Gallotannins, Rottlerin, Lupeol, Curcumin, etc. have shown significant effect in combating renal injury which is an early event in nephrolithiasis. These findings point towards a great potential for the therapeutic application of antioxidants and free radical scavengers to reduce stone occurrence particularly under hyperoxaluric conditions. This review article attempts to compile various naturally occurring antioxidants used in treatment of nephrolithiasis. Keywords: Calcium oxalate, Oxidative stress, Hyperoxaluria, Reactive oxygen species, antioxidants